The Release of AASB 1041 “Revaluation of Non-Current Assets” and Stock Price Behaviour - Sundalangi, Elvis (JBE (Journal of Business and Economics); Volume 9 No.1, 2010 JBE UNKLAB, 2010)
This paper examines stock price behavior during the release of Australian Accounting Standards Board (AASB) 1041 “Revaluation of Non-Current Assets”. ASSB 1041 requires frequent revaluations (the standard suggests a three-year cycle) of a class of assets once revaluation is adopted for that class of assets. Assets revaluations are expensive due to the revaluation fees; hence, the requirement to revalue at least once in three years will increase the cost of revaluation activity. it is therefore expected that stock prices will react negatively towards the release of AASB 1041. The paper hypothesizes abnormal returns to be significantly lesser in the months surrounding the announcement month. The finding confirms the prior expectation that stock prices performed negatively during the release of AASB 1041. The statistical test found the abnormal returns surrounding the months of announcement to be significantly lesser than the months leading and subsequent to the announcement months.